The Effect Of Exercise Habits On Stress Level - Muzakir, Muzakir (Malikussaleh University, Aceh, Indonesia, 2021)
Stress is a negative emotional experiences are accompanied by changes in biochemical, physiological, cognitive and behavioral predictability. Stress can also be interpreted as a condition that suppresses psychological state of a person in reaching an occasion in which to achieve this occasion there is a limit or barrier. Sport Habits is a physical activity that is planned, structured, and done repeatedly and intended to improve or maintain physical fitness. The purpose of this study to determine the influence of sports habits toward the level of stress on students of the Faculty of Medicine, University XYZ. This study is a descriptive and analytical. The population in this study were all students of the Faculty of Medicine, University XYZ totaling 220 people with a sample of 72 people. The sampling technique used was stratified consecutive sampling. The data collected by distributing questionnaires, data processing using computer statistics program and analyzed using bivariate using Chi Square test. The results of this study indicate that the majority of respondents (62,5%) did not have a habit of exercise and also the majority of respondents experiencing moderate stress (51,4%). Chi Square test results show the value of p = 0,000 ( p0,05) so there is the influence of the sport habits toward stress levels